Calculation of inductance and capacitance in power system transmission lines using finite element analysis method - Illias, Hazlee Azil; Bakar, Ab Halim Abu; Mokhlis, Hazlie; Halim, Syahirah Abd (Obliczenia indukcyjności i pojemności linii przesyłowej z wykorzystaniem metody elementu skończonego, 2012)
In power system, every transmission line exhibits many electrical properties. Analytical method has been widely used in determination of the inductance and capacitance for various transmission line configurations. However, it not applicable in general especially for complicated conductor arrangements. Therefore, in this work, a magnetic flux-linkage finite element analysis (FEA) method has been proposed to calculate the inductance in various conductor arrangements in different transmission line configurations while the capacitance is calculated using electric potential FEA method.